THE INFLUENCE OF BODY TYPE, STRENGTH, AND FLEXIBILITY ON INJURY OCCURRENCE AMONG STOK BINA GUNA STUDENTS IN ARTISTIC GYMNASTICS SUBJECT - Lubis, Hafiz Yazid; Isnandar, Muhammad; Waruwu, Rahmad Sentosa; Sillaban, Putra Anugrah (Gladi : Jurnal Ilmu Keolahragaan, 2024)
Objectives—This pilot project, aimed at investigating body type, strength, and flexibility as risk factors for injury amongst Bina Guna College of Sports and Health Students, has yielded significant findings. Methods—Fifteen subjects volunteered to participate in the present study. An ex-post facto study design using independent samples was employed. Injury history was established through the use of a questionnaire. From this information, each individual's injury status was categorized as "high" or "low" using a previously designed and validated scoring system. Body-type ratings were determined, followed by tests to assess muscular endurance, strength, and flexibility. Results—A multivariate analysis of variance (MANOVA) revealed no significant difference between groups of low and high injury rates and the dependent variables selected. However, the univariate analysis suggested trends indicating that the low-injury subjects were more flexible (back extension and ankle dorsiflexion) than those who reported more injuries (P=0.013). Independent t-tests revealed that between groups of low and high injury rates, there were significant age differences (P=0.002), stature (P=0.006), body mass (P=0.001), and years of gymnastics training (P=0.016). Conclusions—In the present study, strength, and body type proved not to be good indicators of an individual's susceptibility to injury. However, trends suggest low flexibility levels may predispose a gymnast to injury. The incidence of injury may also be related to the number of years an individual has participated in competitive gymnastics. In addition, older, taller, and heavier gymnasts may be at greater risk of injuries. These findings are crucial for the development of tailored training methods and injury prevention strategies, and they have significant implications for coaches in selecting and training future gymnasts